ELECTORAL MANIPULATION STRATEGIES IN TURKEY DURING THE AKP RULE - Martin Dudáš (Trames, 2024)
This article analyses strategies of electoral manipulation employed by the regime of Recep Tayyip ErdoÄan in Turkey. Three long-term methods and three short-term methods are examined, the former being unequal access to resources, media and law, and the latter being election fraud, intimidation of opposition, and vote buying. The text argues that the Turkish government employs primarily long-term strategies, but short-term ones are also present and thus should not be ignored. State resources are being siphoned to municipalities controlled by AKP and regime-friendly businessmen who then provide donations and other favors for the party. State media and media regulators came under the regimeâs control, resulting in minimal coverage of the opposition in both public and most private media outlets. The takeover of the judiciary and vague definitions in the Anti-Terror law and other laws were used to suppress opposition politicians and journalists. It also allowed the regime to take control of bodies overseeing elections, leading to malpractice. Intimidation of opposition had a form of both legal prosecution and physical attacks and focused primarily on pro-Kurdish parties. Vote buying in Turkey seems mainly to be a form of rewarding voters of the ruling party, not an attempt to persuade swing voters.